2020
DOI: 10.1016/j.jor.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon complex: The anatomy of its insertional footprint on the calcaneus and clinical implications

Abstract: The Achilles tendon is the largest, and most commonly torn tendon in the body. The Achilles is usually torn at a region of relative hypo-vascularity proximal to its insertion. However, partial thickness tears and other pathologies often occur at its insertion on the calcaneus. Anatomically, the insertion is a confluence of the gastrocnemius and soleus muscles that fuse to form a myotendinous unit on the posterosuperior aspect of the calcaneus. This review aims to reveal the insertional footprint as individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In general, for surgical reconstruction it has to be considered that the Achilles tendon is formed by the confluence of the tendons of the soleus and both gastrocnemius muscles. These subtendons intertwine and twist towards their distal insertion and have a specific arrangement in the midportion and the insertion of the calcaneus [ 5 , 17 ]. Based on the anatomic region within the tendon, partial ruptures might be assigned to the specific subtendon, which might lead to an isolated partial hypotrophy of the gastrocsoleus muscle complex with reduced voluntary electromyography activity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, for surgical reconstruction it has to be considered that the Achilles tendon is formed by the confluence of the tendons of the soleus and both gastrocnemius muscles. These subtendons intertwine and twist towards their distal insertion and have a specific arrangement in the midportion and the insertion of the calcaneus [ 5 , 17 ]. Based on the anatomic region within the tendon, partial ruptures might be assigned to the specific subtendon, which might lead to an isolated partial hypotrophy of the gastrocsoleus muscle complex with reduced voluntary electromyography activity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…These subtendons intertwine and twist towards their distal insertion and have a specific arrangement in the midportion and the insertion of the calcaneus [ 5 , 17 ]. Based on the anatomic region within the tendon, partial ruptures might be assigned to the specific subtendon, which might lead to an isolated partial hypotrophy of the gastrocsoleus muscle complex with reduced voluntary electromyography activity [ 17 ]. Partial tears mostly occur in the posterior mid-tendon 3–4 cm above the superior calcaneus, whereas a further study demonstrated that intratendinous tears are mostly anterior and medial, which mostly present fibers of the soleus and lateral gastrocnemius components [ 8 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…No large-scale MRI studies such as this have been previously reported. We studied the Achilles tendon between the lower outline of the soleus muscle belly to the level of the calcaneal tuber, which includes the zone where tendinopathy and ruptures most often occur 2 , 8 , 22 . Active tracking of the subtendons from the myotendinous junction, distal to the calcaneus, showed the same twisted structure of the Achilles tendon as revealed previously 5 , 10 , 17 , 18 , 20 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…retrocalcaneal bursitis or Haglund deformity. This area is also quite sensitive to partial injuries causing isolated laxity of the tendon 22 . The largely uniform structure of the Achilles tendon is only apparent because the nonuniform function of the Achilles tendon occurs during movement and exercise 23 and internal tendon tears are longitudinal in direction 24 .…”
Section: Side and Gender Value S-mgc S-lgc S-solmentioning
confidence: 99%
“…Since the recognition and reporting of subtendons, there has been a surge in tendon and subtendon research, including imaging (Handsfield et al, 2017 ; Clark and Franz, 2020 ), computational modeling (Handsfield et al, 2017 ; Shim et al, 2018 ), anatomical dissection (Pekala et al, 2017 ; Mahan et al, 2020 ), and experimental approaches (Finni et al, 2018 ; Maas et al, 2020 ). Structurally, the subtendons display an internal torsion or twisting, which can be seen by the naked eye by observing the trajectory of collagen fascicles within the Achilles (White, 1943 ; van Gils et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%